Effect of presheath electron temperature on magnetized plasma-wall transition and wall sputtering by plasma having two species of positive ions. (16th March 2020) - Basnet, Suresh; Sarma, Arun; Khanal, Raju
Abstract: In this work, the kinetic simulation method has been employed to study the effect of presheath electron temperature on plasma-wall interaction mechanism and its consequence on wall sputtering. Multi-component plasma interacts with tungsten (W) surface through non-neutral plasma sheath formed near the Plasma Facing Material (PFM). It is assumed that two ion species have different temperatures with same degree of ionization. We have examined the ion velocity distributions in front of the material wall. The thermal velocity of electron at the presheath-sheath interface determines the dimension of Debye sheath and hence energy flow towards the wall. The obtained results of the present work conclude that the angle of incidence at the wall and its sputtering rate is highly affected by electron temperature at the presheath-sheath boundary.